Controlled synthesis of magnetic nanoparticles and their functional properties - Ow Yong, Wai Kae. (2009)
Due to its distinctive properties compared to their bulk counterparts, studies of monodisperse magnetic nanoparticles have been carried out intensively over the past decade. These nanoparticles can be used in several applications. Properties of magnetic nanoparticles can be tuned by controlling the synthesis parameters. Spinel ferrite structures have a complex cubic unit cell with close-packed oxygen arrangement. Cobalt ferrites (CoFe2O4) nanoparticles have been successfully produced by the organic phase decomposition of metal precursors under high temperature of 260°C. The nanoparticles were characterized by SEM-EDX, XRD, VSM and TEM. Results have shown that CoFe2O4 particles are superparamagnetic and the saturation magnetization of the nanoparticles increases with synthesis reaction time.